Conversion therapy strategy: A novel GPC3-targeted multimodal organic phototheranostics platform for mid-late-stage hepatocellular carcinoma - Fan Wu; Xin Kuang; Sanlin Deng; Shuo Qi; Jian Xiong; Bibo Zhao; Chuanfu Li; Senyou Tan; Qiang Kang; Hao Xiao; Xiaofeng Tan; Gui-long Wu; et al. (Materials Today Bio)
Hepatocellular carcinoma (HCC) is typically diagnosed at intermediate to advanced stage, making surgical treatment unfeasible. Conversion therapy aims to reduce tumor stage, improve hepatic resection feasibility, and lower recurrence rates. Since traditional therapies are often accompanied by uncertainty of efficacy, there is an urgent need to explore new treatment strategies. Near-infrared phototheranostics technology provides a new way for HCC diagnosis and treatment by its excellent optical properties. However, complex preparation and poor biocompatibility of phototheranostics probes limit clinical application. In this study, we developed a fluorescence/magnetic resonance dual-modality imaging (FLI/MRI) as well as photothermal/photodynamic therapy (PTT/PDT) GPC3-targeted multifunctional phototheranostics probe, IR820-GPC3-Gd NPs (IGD NPs), to improve the efficiency of conversion therapy for HCC. The IGD NPs were simply prepared with the IR820 as the core. Conjugating the HCC-specific targeting molecule GPC3 peptide and the MRI agent DOTA-Gd through click chemistry. IGD NPs target HCC cells through GPC3, releasing heat and reactive oxygen species (ROS) under noninvasive 808 nm laser irradiation to reduce tumor size and achieve downstaging. High-sensitivity FLI/MRI precisely delineates tumor boundaries, providing real-time surgical navigation and prognosis assessment. This novel probe offers a feasible and effective treatment option for advanced HCC.